Maternal Nutrition Knowledge and Complementary Feeding Intake in Wasting and Non-Wasting Children Aged 6–24 Months in the Ganting Community Health Center Area, Gedangan, Sidoarjo - Ahkamia Adila Putri; Amalia Ruhana (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Wasting in children aged 6-24 months remains a nutritional problem that requires attention because it can hinder their growth and development. This study aims to analyze differences in maternal nutritional knowledge and complementary feeding intake in wasting and non-wasting children aged 6-24 months in the Ganting Community Health Center, Gedangan, Sidoarjo. The study used an observational analytical quantitative design with a matched case-control approach. The study population was children aged 6–24 months and their mothers. The sample consisted of 66 respondents, namely 33 wasting children and 33 non-wasting children, selected through purposive sampling and individual matching based on age and sex. Data were collected using a maternal nutritional knowledge questionnaire, a single 24-hour dietary recall, and anthropometric measurements. Data analysis was performed univariate analysis and bivariate analysis using the McNemar test and the Odds Ratio (OR) with a 95% confidence level. The results showed a significant difference in maternal nutritional knowledge (p=0.003; OR=5.66) and fulfillment of the Minimum Acceptable Diet (MAD) (p=0.019; OR=3.75) between the wasting and non-wasting groups. This study found, low maternal nutritional knowledge and failure to meet the Minimum Acceptable Diet (MAD) was associated with an increased risk of wasting among children aged 6-24 months